Praças públicas: aspectos da gestão e mapeamento desses espaços no município de São Paulo, SP - Benchimol, Juliana Furlaneto (2015)
The presence of green areas in cities provides many benefits to both the population and the environment. Studies about public squares contribute to public management and urban sustainability, since these areas play an important social and environmental role. Through interviews with public officials and analysis of the results using the Collective Subjet Discourse (CSD) method, the aim of this work was to elucidate the function and management aspects of São Paulo’s squares in the view of public authorities. This research reveals the need for, although the management of the squares of the city of São Paulo is under the responsibility of separate boroughs that make up the city government, the data on São Paulo squares must be disclosed and analyzed centrally in order to promote a more efficient management and guide the creation of new spaces of this nature, especially in the regions which are more needy. There is no evidence that there is planning, organization, direction and control (management model) of the public squares in Sao Paulo. The role of government agencies is operational. The decentralization in the management of these public spaces, in the one hand is positive as it gives autonomy and agility to boroughs in the implementation, but otherwise can make it difficult, because they depend on planning and control of resources coming from other municipal bodies, which are not involved directly. One of the challenges mentioned, therefore, is the implementation of a management system to give functionality to these integrative elements - the squares, upon completion of the deployment phase of the Green Areas System (SAV) already started. One aspect highlighted in this work is the need for an inventory, still non-existent, of urban green areas, so that, from there, create a consistent administrative process driven by the reality of each sub region. The results presented here show that the squares exert essentially a social function. There is still no consensus about the environmental role that they may exercise, despite the very qualified professionals to manage these areas as such.